Etiological and molecular profile of pathogens causing clinical mastitis, and antimicrobial use in dairy herds - Tomazi, Tiago (2017)
The general objectives of this thesis were: (i) to determine the etiological and molecular profile of clinical mastitis (CM) in 20 dairy herds of Southeast, Brazil; and (ii) to quantify antimicrobial used for treatment of CM in the study population. To achieve this goals, four studies were performed. In the Study 1, we characterized the pathogen frequency and severity of CM in dairy herds. In addition, we determined the incidence rate of clinical mastitis (IRCM) and its association with the following herd-level descriptors: bulk milk somatic cell count (BMSCC), bulk milk total bacterial count (BMTBC), herd size (number of lactating cows), milk yield, housing system and season. The association between herd-level descriptors and IRCM were determined by two groups of mixed regression models: one based on the overall IRCM, and five based on the following specific-pathogen groups: contagious, other Gram-positive, Gram-negative, other (composed of yeast and Prototheca spp), and negative culture. A total of 5,957 quarter-cases of CM were recorded and the most frequently isolated pathogens were Escherichia coli (6.6% of total cultures), Streptococcus uberis (6.1%), and Streptococcus agalactiae (5.9%). The majority of CM cases were mild (60.3%), while 34.1% were moderate and 5.6% severe. Overall, the IRCM was 9.7 quarter-cases per 10,000 quarter-days at risk (QDAR), and the only herd-level parameter associated with overall IRCM was BMSCC, in which the highest IRCM was observed for herds with BMSCC >600.000 × 103 cells/mL. In the models evaluating the specific-pathogen groups, IRCM with isolation of major contagious pathogens was associated with BMSCC, milk yield and housing system. For the evaluation of other Gram-positive pathogens, the IRCM was higher in the rainy season of 2015 in comparison with the other seasonal categories. In addition, for the model evaluating the Gram-negative group, the IRCM was highest in herds with BMTBC >30 × 103 cfu/mL. The Study 2 aimed to characterize the treatment profile and quantify the antimicrobial consumption for treatment of CM in dairy herds; and to determine the association of antimicrobial use (AMU) and the same herd-level descriptors as described in the Study 1. Data on treatment practices and AMU were obtained from 19 dairy herds for a period of 12 months per herd. The AMU for treatment of CM was quantified monthly in units of defined daily dose (DDD) and expressed as antimicrobial treatment incidence (ATI; number of DDD per 1,000 lactating cows-day). The overall monthly mean ATI was 17.7 DDD per 1,000 lactating cow-days (15.4 for intramammary compounds, and 2.2 for systematically administered antimicrobials). Among intramammary drugs, aminoglycosides had the highest ATI (11.7 DDD per 1,000 lactating cow-days), while for systematically administrated antimicrobials, fluoroquinolones (4.2 DDD per 1,000 lactating cow-days) were the most frequently used antimicrobials. Herd size and BMSCC were positively associated with ATI. In addition, herd-level ATI was higher in freestall herds than in compost bedded-pack barns. In the Study 3, we determined the phylogeny of E. coli strains isolated from CM in dairy cows and the association of most frequent phylogroups with antimicrobial susceptibility. A total of 100 E. coli isolates recovered from CM cases described in the Study 1 were categorized according to their phylogenetic group using a quadruplex PCR method; antimicrobial susceptibility pattern was also evaluated. Most isolates were assigned to phylogenetic group A (52%), followed by B1 (38%), B2 (2%), C (4%), D (3%), and E (1%). Resistant isolates were observed for all evaluated antimicrobials. Overall, more than 96% of E. coli isolates were resistant to ampicillin, and more than 23% were resistant to cephalothin, sulphadimethoxine or tetracycline. High levels of resistance (>70%) were also found to erythromycin, oxacillin, penicillin, penicillin associated with novobiocin, and pirlimycin. In contrary, high susceptibility was observed to ceftiofur (96.8%) among E. coli isolates. Difference in the antimicrobial susceptibility among phylogenetic groups was observed only for cephalothin, in which E. coli strains belonging to the phylogroup A were inhibited at lower antimicrobial concentrations than strains assigned to the phylogroup B1. In Study 4, we evaluated the genotypic diversity among Strep. agalactiae and Strep. uberis isolates recovered from CM in dairy cows; in addition, the study evaluated the association of genotypes clustered by genetic similarity with antimicrobial susceptibility pattern. Isolates were subtyped using randomly amplified polymorphic DNA (RAPD) analysis. A great genotypic diversity was found for both Strep. agalactiae (45 subtypes out of 89 isolates) and Strep. uberis (56 subtypes out of 88 isolates). For evaluation of antimicrobial susceptibility, subtypes of Strep. agalactiae were clustered into three groups (Ia, Ib and II), while Strep. uberis subtypes were clustered into two groups (I and II) according to their genetic similarity. Overall, Strep. agalactiae isolates showed high susceptibility to most antimicrobials, except to tetracycline and erythromycin. Differences in the antimicrobial susceptibility among clusters of Strep. agalactiae were observed for ampicillin, ceftiofur, erythromycin, pirlimycin, sulphadimethoxine and tetracycline. In contrary, Strep. uberis isolates were categorized as resistant to most antimicrobials, except to cephalothin and penicillin+novobiocin. No differences were observed among clusters for all antimicrobials in the analysis of Strep. uberis. In conclusion, the results of this thesis indicated a high IRCM in the evaluated herds, and although environmental pathogens were the most common cause of CM in these herds, contagious pathogens such as Strep. agalactiae and Staph. aureus, are still a concern in some dairy herds of Brazil. Furthermore, high frequencies of AMU and off-label protocols were observed among the evaluated herds. The non-judicious use of antimicrobials can become a risk factor for the development of antimicrobial resistance, which was even observed for isolates belonging to the three most prevalent bacterial species identified from CM cases in our study (E. coli, Strep. agalactiae and Strep. uberis). Finally, because there were some herd-level descriptors associated with the IRCM and AMU in our study, there may be opportunity for management strategies aiming to improve the control of CM in dairy herds of southeastern Brazil.